Cardiac Resynchronization Therapy in Patients With Heart Failure and Left Bundle Branch Block - Polishchuk, D. V.; Nakonechnyi, S. Yu.; Molodan, O. V.; Nykonenko, O. S. (Transplantation and artificial organs, 2025)
The purpose. To determine the efficacy, safety, and potential advantages of two variants of cardiac resynchronization therapy–biventricular pacing CRT(D) and selective left bundle branch pacing (LBBP) – in patients with left bundle branch block (LBBB) and heart failure. Materials and Methods. In the first group, cardiac resynchronization therapy devices (CRT-(D)) were implanted in 24 patients using the standard biventricular pacing technique. The patients were aged 36 to 72 years; 20 were male and 4 were female. Three leads were positioned in the heart chambers: the atrial lead in the right atrial appendage, ventricular leads in the interventricular septum or apex, and in a lateral cardiac vein to stimulate the left ventricle in the region of maximal electromechanical delay. In the second group, 26 patients aged 16 to 75 years (21 males, 5 females) underwent selective left bundle branch pacing (LBBP). Transseptal selective LBBP was performed using an active-fixation lead (Selekt Secure, 69 cm) and a C315HIS delivery system. Central cardiohemodynamic parameters–end-systolic volume (ESV), end-diastolic volume (EDV), and left ventricular ejection fraction (LVEF) by Simpson’s method, as well as pulmonary artery pressure–were assessed by transthoracic echocardiography (TTE). The effectiveness of ventricular resynchronization was evaluated using speckle-tracking echocardiography. The following parameters were calculated: left ventricular longitudinal strain (4-chamber view), circular strain at the basal and apical segments, and the time to peak systolic contraction of LV segments (MOWD). Changes in QRS morphology after resynchronization therapy in both groups were assessed using standard ECG. A 6-minute walk test was performed before surgery and at 3, 6, and 12 months post-procedure to evaluate the distance covered at a comfortable walking pace on a flat surface. Results. The observation period lasted 12 months. After standard biventricular resynchronization pacing, QRS duration decreased by 21%, from 158 ± 7.1 ms to 125.3 ± 5.1 ms (St–R interval 115 ± 5.1 ms). After selective LBBP, the St–R interval was 82.3 ± 7.1 ms, representing a 47% reduction in QRS duration compared with baseline. Changes in central hemodynamic parameters over 12 months were as follows: in the first group (CRT-D), LVEF increased from 27.3 ± 3.8% to 45.2 ± 4.3%; in the second group (LBBP), LVEF increased from 39.3 ± 3.8% to 48.5 ± 3.2%. This corresponds to a 40% and 18% increase in LVEF in the first and second groups, respectively. A reduction in EDV of 28% (from 265.2 ± 14.7 to 191.3 ± 14.4 ml) was observed in the first group, and an 11.8% reduction (from 203.2 ± 13.4 to 179.3 ± 12.9 ml) in the second group. Hemodynamic improvements also included reductions in ESV: 36.5% (from 148.2 ± 3.4 to 94.2 ± 3.37 ml) and in systolic pulmonary artery pressure by 43.3% (from 30.3 ± 4.1 to 23.2 ± 3.8 mmHg) in the first group. In the second group, ESV decreased by 25.2% (from 127.5 ± 2.7 to 95.4 ± 3.1 ml), and systolic pulmonary artery pressure decreased by 14% (from 37.4 ± 3.9 to 32.4 ± 3.5 mmHg). Speckle-tracking echocardiography demonstrated significant improvement in left ventricular deformation patterns–both longitudinal and circumferential–in both groups. Conclusion. Both techniques are effective in restoring left ventricular contractility and can be used in this group of patients. However, there are inherent advantages of direct bundle branch block pacing: it significantly shortens QRS duration, as our results showed, there were no failed electrode placement attempts, which even required thoracotomy with biventricular pacing. Left bundle branch block pacing offers several potential advantages over biventricular pacing , including lower pacing thresholds, no atrial capture, and less technical complexity.